UiTM Law Newsletter (May - Aug 2019) - UiTM Shah Alam, Faculty of Law (Faculty of Law, 2019)
As we release our second e-newsletter, we continue to highlight and illustrate numerous programs and achievements occurring within UiTM Law. Our activities continue to broaden and deepen our reputation in response to the internationalisation of the education fraternity in Malaysia. Among our many initiatives, one that warrants mention is the 17th IUCN Academy of Environmental Law Colloquium hosted by UiTMLaw in August 2019. Hosting IUCN 2019 is yet another important milestone in UiTMLaw's commitment to embark on global collaborative undertakings in the field of environmental law, governance and policy, continuing a tradition of bringing together academics, researchers and professionals from all over the world. September is humming with new energy and renewed commitment. It is a pleasure to continue to serve this chapter, and I am looking forward to what the new academic year brings.